In situ synthesis of phosphate binding mesocellular siliceous foams impregnated with iron oxide nanoparticles - Tong, C.; Eroglu, Ela; Raston, C. (2014)
Mesocellular siliceous foams (MCFs) loaded with preformed magnetite nanoparticles ca. 8 nm in diameter are readily prepared in water under neutral conditions. The calcined composite nanomaterial with 0.72% weight of iron is effective for the adsorption of phosphate ions from liquid effluents, with the overall adsorption capacity maintained on cycling five times, up to 79.2 mg PO4 3- per gram Fe.